Imagining gender, nation and consumerism in magazines of the 1920s - Alexander, Rachael (Anthem studies in book history, publishing and print culture., 2022)
"Offering the first comparative study of 1920s' US and Canadian print cultures, Imagining Gender, Nation and Consumerism in Magazines of the 1920s examines the highly influential Ladies' Home Journal (1883-2014) and the often-overlooked Canadian Home Journal (1905-1958). American magazines were, in the main, established earlier than their Canadian counterparts, and the Ladies' Home Journal was pioneering in the development of the stylistic and economic model of the modern mass-market magazine. Unsurprisingly the Canadian Home Journal -- and Canadian magazines more generally -- made use of the tried-and-tested methods developed south of the 49th parallel. This, combined with comparatively far smaller circulations, has led to the unflattering assumption that Canadian magazines were merely derivative of their American predecessors. The present book argues that this is not the case, but that both magazines make use of -- and manipulate -- the conventions of the magazine form in notably different ways, as they work to construct their imagined audiences."--